Penggunaan Hermeneutika dalam Penelitian Manajemen - M. Syamsul Hidayat (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
One of the methods used to assist in analyzing and interpreting qualitative data is hermeneutics. The role of Hermeneutics can be very important in the development of qualitative research, including in the field of management. The use in such research can be in the form of Prejudice Hermeneutics or Critical Hermeneutics. Hermeneutics helps researchers to interpret and analyze text, where the text can be in the form of computer data diagrams, company reports or other forms so that it makes sense and can be used in management decision making. However, the use of hermeneutics allows qualitative researchers to describe organizational complexity and view it from many good aspects. from a social, cultural and political perspective.